Energy-saving COVID–19 biomedical plastic waste treatment using the thermal - Catalytic pyrolysis. (1st February 2023) - Choudhary, Rajesh; Mukhija, Abhishek; Sharma, Subhash; Choudhary, Rohitash; Chand, Ami; Dewangan, Ashok K.; Gaurav, Gajendra Kumar; Klemeš, Jiří Jaromír
Abstract: The rate of Biomedical waste generation increases exponentially during infectious diseases, such as the SARS-CoV-2 virus, which burst in December 2019 and spread worldwide in a very short time, causing over 6 M casualties worldwide till May 2022. As per the WHO guidelines, the facemask has been used by every person to prevent the infection of the SARS-CoV-2 virus and discarded as biomedical waste. In the present work, a 3-ply facemask was chosen to be treated using the solvent, which was extracted from the different types of waste plastics through the thermal–catalytic pyrolysis process using a novel catalyst. The facemask was dispersed in the solvent in a heating process, followed by dissolution and precipitation of the facemask in the solvent and by filtration of the solid facemask residue out of the solvent. The effect of peak temperature, heating rate, and type of solvent is observed experimentally, and it found that the facemask was dissolved completely with a clear supernate in the solvent extracted from the (polypropylene + poly-ethylene) plastic also saved energy, while the solvent from ABS plastic was not capable to dissolute the facemask. The potential of the presented approach on the global level is also examined. Graphical abstract: Image 1 Highlights: Estimation of plastic waste and biomedical waste in India and at the global level. Plastic waste upgraded to liquid oil through thermal–catalytic pyrolysis process. GC and FTIR-spectrometry analysis conducted to identify the composition of oil. The extracted oil used as solvent to disinfect shredded biomedical waste by heating. Solvent from PP plastic found efficient for BMW treatment in more than 01 cycle.